MANAJEMEN PEMBELAJARAN DI PONDOK PESANTREN PEMBANGUNAN MIFTAHUL HUDA MAJENANG KABUPATEN CILACAP - Mahfud, Muntaha (Jurnal El-Hamra : Kependidikan dan Kemasyarakatan, 2019)
Islamic boarding school is as a religious education institution. It is supported by a set of curriculum that acts as a motivator in teaching and learning. In general, the curriculum used on it is being the reference of certain learning, and manifested in the form of determining certain yellow books in accordance with the level of knowledge of students by usingmastery learning model. This study has three objectives: 1) learning management on aspects of planning, implementation and assessment; 2) obstacles in the implementation of learning; and 3) solutions undertaken toovercome obstacles in yellow book study at Pondok Pesantren Miftahul Huda Pembangunan Majenang Cilacap. The findings related to learning management at Pondok Pesantren Pembangunan Miftahul Huda Majenang are: 1) every early year of caregiver lessons and ustadz(the term address for islam teachers)plan the learning activities by setting learning schedule; 2)teaching schedule is made by the principle of deliberation,and involving all people of pesantren; 3) the implementation of learning is done on a predetermined schedule; 4) the assessment of learning as a benchmark of success has not been done comprehensively and routinely.The whole learningmanagement which is held at Pondok Pesantren Pembangunan Miftahul Huda Majenang runs optimally.Key Words: management, learning, islamic boarding school